RGS10 mitigates high glucose-induced microglial inflammation via the reactive oxidative stress pathway and enhances synuclein clearance in microglia - Chung, Jaegwon; Jernigan, Janna; Menees, Kelly B.; Lee, Jae-Kyung (Frontiers in Cellular Neuroscience, 2024)
Microglia play a critical role in maintaining brain homeostasis but become dysregulated in neurodegenerative diseases. Regulator of G-protein Signaling 10 (RGS10), one of the most abundant homeostasis proteins in microglia, decreases with aging and functions as a negative regulator of microglia activation. RGS10-deficient mice exhibit impaired glucose tolerance, and high-fat diet induces insulin resistance in these mice. In this study, we investigated whether RGS10 modulates microglia activation in response to hyperglycemic conditions, complementing our previous findings on its role in inflammatory stimuli. In RGS10 knockdown (KD) BV2 cells, TNF production increased significantly in response to high glucose, particularly under proinflammatory conditions.Additionally, glucose uptake and GLUT1 mRNA levels were significantly elevated in RGS10 KD BV2 cells. These cells produced higher ROS and displayed reduced sensitivity to the antioxidant N-Acetyl Cysteine (NAC) when exposed to high glucose. Notably, both BV2 cells and primary microglia that lack RGS10 exhibited impaired uptake of alpha-synuclein aggregates. These findings suggest that RGS10 acts as a negative regulator of microglia activation not only in response to inflammation but also under hyperglycemic conditions.